Antibacterial and biocompatible properties of polyurethane nanofiber composites with integrated antifouling and bactericidal components. (28th April 2016) - Shi, Hengchong; Liu, Haiyu; Luan, Shifang; Shi, Dean; Yan, Shunjie; Liu, Chunmei; Li, Robert K.Y.; Yin, Jinghua
Abstract: A facile, low-cost and time-saving method was proposed to prepare antibacterial polyurethane- g -polyethylene glycol (TPU-g-PEG) nanofiber composite by anchoring silver nanoparticles (AgNP) onto nanofibers via ultrasonication assistance. Firstly, antifouling PEG as bacteria-repelling component was chemically grafted onto TPU nanofibers through UV photo-graft polymerization to obtain TPU-g-PEG nanofibers; then AgNP as bactericidal component were immobilized onto the TPU-g-PEG nanofibers under the assistance of ultrasonication. Even if the nanofibers were immersed into PBS solution and incubated for 7 days, the released content of AgNP characterized by ICP-MS was 2.688 μg which was much lower than that of reference reported method. The TPU-g-PEG/Ag nanofiber composites exhibited excellent hemocompatibility, including suppression of platelet and red blood cell adhesion, the lower hemolysis ratios, and the higher blood clotting index. Importantly, the as-prepared nanofiber composites performed better antibacterial properties in vitro assays employing gram negative and positive strains, because of the bacterial resistance of the grafted PEG and the bactericidal effect of silver. Our approach has significant potential for the development of infection-resistant wound dressing.